DESIGN AND IMPLEMENTATION OF INTELLIGENCE SYSTEM FOR POTHOLES DETECTION USING LABVIEW - M., Arivalagan; M., Lavanya; D., Vijayanandh; A., Manonmani (International Journal of Psychosocial Rehabilitation, 2020)
Vehicles are an important way of transportation all over the world. There are many cases of road accidents every day in the world. Such accidents are the main reason for traffic jams on the road, consequently resulting in a loss of valuable time. One of the main problems in developing countries is the maintenance of roads. Well-maintained roads contribute a serious portion to the country’s economy. Identification of pavement distress like potholes not only helps drivers to avoid accidents or vehicle damages. The frequency of road accidents is extremely high, which causes tons of injury to human life and valuable properties. The number of accidents is extremely high in hilly and fog-affected areas. Many road accidents are caused by a collision between vehicles due to the inability of the drivers to gauge the perimeter of their vehicles, and the other reason is unawareness of nearby vehicles. This project introduces a GPS-based system that actively and continuously sends vehicle location coordinates (latitude/longitude) to the LabVIEW, which processes/analyses data from all such vehicles, predicts potential collisions, and sends a back alert to the vehicle to raise a visual/sound alert.